2019
DOI: 10.1139/cjm-2018-0366
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the correlation between biochar amendment and shifts in bacterial community 4 years after a single incorporation in soybean- and maize-planted soils in northeastern China

Abstract: To date, there have been few reports examining the correlation between biochar treatments, crop species, and microbiome shifts. In this study, shifts in the soil bacterial community were investigated 4 years after a single incorporation of biochar in soils planted with soybeans and maize. Clear changes in the bacterial community composition and structure were detected in the soybean-planted soil amended with low-titer biochar (7.89 t/ha), whereas such changes in the maize-planted soil were not observed at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The application of DS hampers the mineralization of organic matter. However, with higher biochar doses, the soil retains moisture for longer periods [ 50 ], facilitating efficient enzymatic activities and subsequently enhancing organic matter content [ 51 ]. Adequate soil moisture is crucial not only for plant growth but also for stimulating various humification processes within the soil [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of DS hampers the mineralization of organic matter. However, with higher biochar doses, the soil retains moisture for longer periods [ 50 ], facilitating efficient enzymatic activities and subsequently enhancing organic matter content [ 51 ]. Adequate soil moisture is crucial not only for plant growth but also for stimulating various humification processes within the soil [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soil microbes are active contents that can improve soil fertility by impacting on the microbial community structure in rhizosphere soil and its nutrient cycling [25]. Previous studies suggested that soil microbial biomass could be increased in soil supplemented with biochar and that the microbial community structure and abundance were changed over time [26]. Both soil microbes, Ochrobactrum sp.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of biochar at different pyrolysis temperatures have different adsorption types and environmentally persistent free radicals, which also affect the population and abundance of different soil microorganisms. All these factors affect the degradation behavior of pesticides in soil, [66][67][68][69][70] therefore the mechanism of biochar affecting AITC degradation needs to be further explored. Liu et al also showed that with the increase in pyrolysis temperature, biochar made from Michelia alba wood accelerated the degradation of CP in soil.…”
Section: Soil Amendmentsmentioning
confidence: 99%